Pharmacological inhibition of lipolysis prevents adverse metabolic outcomes during glucocorticoid administration - Melissa A. Linden; Susan J. Burke; Humza A. Pirzadah; Tai-Yu Huang; Heidi M. Batdorf; Walid K. Mohammed; Katarina A. Jones; Sujoy Ghosh; Shawn R. Campagna; J. Jason Collier; Robert C. Noland (Elsevier, 2023)
Objective: Glucocorticoids are one of the most commonly prescribed classes of anti-inflammatory drugs; however, chronic treatment promotes iatrogenic (drug-induced) diabetes. As part of their physiological role, glucocorticoids stimulate lipolysis to spare glucose. We hypothesized that persistent stimulation of lipolysis during glucocorticoid therapy plays a causative role in the development of iatrogenic diabetes. Methods: Male C57BL/6J mice were given 100 μg/mL corticosterone (Cort) in the drinking water for two weeks and were fed either normal chow (TekLad 8640) or the same diet supplemented with an adipose triglyceride lipase inhibitor (Atglistatin - 2  g/kg diet) to inhibit the first step of lipolysis. Results: Herein, we report for the first time that glucocorticoid administration promotes a unique state of substrate excess and energetic overload in skeletal muscle that primarily results from the rampant mobilization of endogenous fuels. Inhibiting lipolysis protected mice from Cort-induced gains in fat mass, excess ectopic lipid accrual, hyperinsulinemia, and hyperglycemia. The role lipolysis plays in Cort-mediated pathology appears to differ between tissues. Within skeletal muscle, Cort-induced lipolysis facilitated diversion of glucose-derived carbons toward the pentose phosphate and hexosamine biosynthesis pathways but contributed to <3% of the Cort-induced genomic adaptations. In contrast, Cort stimulation of lipolysis accounted for ∼35% of the genomic changes in the liver but had minimal impact on hepatic metabolites reported. Conclusions: These data support the idea that activation of lipolysis plays a causal role in the progression toward iatrogenic diabetes during glucocorticoid therapy with differential impact on skeletal muscle and liver.